Barriers to Implementing Comprehensive Sexuality Education as a Strategy to Prevent Adolescent Pregnancy in Indramayu District, Indonesia - Kurnaesih, Een; Herbawani, Chahya Kharin; Febriani, Nelly (Kesmas, 2025)
The implementation of comprehensive sexuality education (CSE) is not optimal. This qualitative study aimed to identify and contextualize barriers to CSE implementation, specifically in Indramayu District, Indonesia. Conventional content analysis procedures were used. Seven participants, consisting of relevant authorities, were interviewed. A purposive sampling technique was employed to select participants. Data were collected through in-depth, semi-structured interviews. All interviews were recorded and transcribed verbatim. Data were analyzed using conventional qualitative content analysis. The barriers to CSE implementation in Indramayu District were identified across five themes: advocacy, technical considerations, coordination and collaboration, integration with other sexual and reproductive health projects, and access beyond school, highlighting the need for improved coordination, targeted outreach, and curriculum development to address these challenges and enhance program effectiveness.